Adenocarcinoma of the Esophagogastric Junction : From Barrett's Esophagus to Cancer - Giacopuzzi, Simone; Zanoni, Andrea; de Manzoni, Giovanni (Springer International Publishing : Imprint: Springer, 2017)
This book offers up-to-date and comprehensive coverage of the diagnosis and therapy of adenocarcinoma of the esophagogastric junction (EGJ). As is appropriate in the era of multidisciplinary and multimodal treatment, the contributions of all the various specialists involved cooperatively in the treatment of EGJ cancer are thoroughly described. Detailed attention is also paid to the significance of preneoplastic lesions, such as Barrett esophagus. The final part of the book represents a surgical atlas documenting the techniques used in the EGJ region, with superb color images and stepwise description of procedures. Against the background of the rapidly increasing incidence in EGJ cancer, especially evident in Western countries, there is a need for greater uniformity in management strategies, which currently vary significantly across the world. This book provides appropriate guidance that will assist all practitioners involved in the diagnosis and treatment of EGJ cancers, including surgeons, oncologists, and radiotherapists.